EVALUATION OF A FEW REPRESENTATIVE ASPECTS FOR THE OCCURRENCE OF VOCAL CHANGES ASPECTS IN THEATER ACTORS (Fiep Bulletin - online, 2011)
Phonation is an ability acquired by the human species. According to Pinho (2001), with evolution, the human being has learned to coordinate organs which, physiologically and anatomically, presented feeding, breathing and protection of the lower airways as their primary functions. Thus, the human voice, in spite of its beauty and improvement, is an adapted function and, as such, it depends on the integrity and balance of the structures of the vocal tract. It is, thus, subject to undergo changes which, often, interferes in communication, especially when dealing with staging theater plays. From this problematic, the object of this study was to evaluate which are the aspects most commonly related to the occurrence of vocal changes in theater actor. It was concluded that vocal problems in theater actors can arise as a result of both environmental factors such as biophysical or emotional issues and that women, on account of organic issues, can suffer voice changes more easily, becoming necessary a vocal preparation work, which includes warm up, strength, resistance and flexibility exercises, of the speech orders, stressing that it must also help in the actor's concentration, attention and memory so that the voice is emitted effortlessly.
Keywords: Evaluation; Vocal Changes; Theater Actor